(untitled) (Eurasian Journal of History, Geography and Economics, 2024)
This article shows the cultural, political and trade relations and interaction of Ustrushona and the development of the Great Silk Road at the height of its prosperity, and the political, cultural and trade relations of Central Asia and other regions also gained importance. passed.